2021
DOI: 10.1002/cbf.3628
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exogenous ciliary neurotrophic factor on cell cycle and neural differentiation markers of in vitro model cells: New insights for future therapeutic approaches

Abstract: Retinoblastoma is known as childhood rare malignancy of the retina. Ciliary neurotrophic factor (CNTF) was previously found to reduce degeneration and promote retina survival. This work investigated the effects of CNTF supplementation on in‐vitro model cells including retinoblastoma (Y79) and adipose‐derived mesenchymal stem cells (AMSCs) viability, proliferation, gene expression and cell cycle. A drop of viability was detected in Y79 treated with CNTF in a dose‐dependent manner (P < .05). However, the prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Another study using adipose-derived mesenchymal stem cells found that low concentrations of CNTF (5 ng/mL) promoted cell proliferation, whereas higher doses (50 and 100 ng/mL) inhibited it. 54 These findings imply that CNTF shows the greatest protective effect on RGCs at a specific concentration, which varies depending on the cell type and developmental stage.…”
Section: Discussionmentioning
confidence: 87%
“…Another study using adipose-derived mesenchymal stem cells found that low concentrations of CNTF (5 ng/mL) promoted cell proliferation, whereas higher doses (50 and 100 ng/mL) inhibited it. 54 These findings imply that CNTF shows the greatest protective effect on RGCs at a specific concentration, which varies depending on the cell type and developmental stage.…”
Section: Discussionmentioning
confidence: 87%